Circulating total testosterone and PSA concentrations in a nationally representative sample of men without a diagnosis of prostate cancer. Issue 11 (28th April 2015) - Peskoe, Sarah B.; Joshu, Corinne E.; Rohrmann, Sabine; McGlynn, Katherine A.; Nyante, Sarah J.; Bradwin, Gary; Dobs, Adrian S.; Kanarek, Norma; Nelson, William G.; Platz, Elizabeth A.
<x xml:space="preserve">Abstract</x> BACKGROUND The association between serum sex steroid hormones and PSA in a general population has not been described. METHODS Included were 378 men aged 40–85 years who participated in the National Health and Nutrition Examination Survey in 2001–2004, who did not have a prostate cancer diagnosis, and had not had a recent biopsy, rectal examination, cystoscopy, or prostate infection or inflammation. Serum total PSA, total testosterone, androstanediol glucuronide (3α‐diol‐G), estradiol, and sex hormone binding globulin (SHBG) concentrations were previously measured. Free testosterone was estimated by mass action. We applied sampling weights and calculated geometric mean PSA concentration by hormone quintiles adjusting for age and race/ethnicity, and also for body mass index, waist circumference, smoking, diabetes, and mutually for hormones. We estimated the OR of PSA ≥2.5 ng/ml per hormone quintile using logistic regression. RESULTS Geometric mean PSA increased across testosterone quintiles after age and race/ethnicity (Q1: 0.80, Q5: 1.14 ng/ml; P‐trend = 0.002) and multivariable (Q1: 0.79, Q5: 1.16 ng/ml; P‐trend = 0.02) adjustment; patterns were similar for free testosterone and 3α‐diol‐G. SHBG was inversely associated with PSA only after multivariable adjustment (Q1: 1.32, Q5: 0.82 nmol/L; P‐trend = 0.01). Estradiol and PSA were not associated. The OR of PSA ≥2.5 ng/ml was 1.54 (95%CI 1.18–2.01) per testosterone quintile after age and race/ethnicity adjustment, and 1.78 (95%CI 1.16–2.73) after multivariable adjustment. CONCLUSIONS In this nationally representative sample, men with higher testosterone had higher PSA even after taking into account other hormones and modifiable factors. Men with higher SHBG had lower PSA, but only after multivariable adjustment. Prostate 75: 1167–1176, 2015. © 2015 Wiley Periodicals, Inc.